(untitled) (Innovaciones Educativas, 2020)
Teacher evaluation at the university level is a process that contributes to the improvement of educational quality. Since it is a complex task, different criteria must be taken into consideration. Also, different aspects such as observations, student’s opinions, colleague’s judgment, and peer review are involved. Students are a consistent source of information. However, since it is the only one, it poses advantages and disadvantages. This work’s main purpose was to get to know the impressions of the teaching and administrative staff and the students on Teacher Evaluation in a private university in Guatemala. By employing a qualitative approach, information was obtained through focus groups. An analysis of the comments’ emergent coding was also carried out, which generated the most important categories. The positive results indicate that, for the teaching staff, the evaluation means an opportunity for professional growth, the anonymity is valued as positive and also the fact that it is carried out online. On the other hand, there is a negative perception about the validity of the evaluation because of the number of participating students, their motivation when answering, and the use given to the results that will negatively impact the work environment. The participants’ general feeling leans towards the redefinition of the evaluation approach so that it is part of continuous improvement.